PENGARUH PRICE PERCEPTION, SALES PROMOTION DAN PRODUCT QUALITY TERHADAP IMPULSE BUYING SKINCARE PRODUCT KONSUMEN PENGGUNA E - COMMERCE SHOPEE GENERASI Z DENGAN SHOPPING LIFESTYLE SEBAGAI MEDIASI - Fachruroji, Tiara Musdhalifah; Padmalia, Metta (Universitas Ciputra Surabaya, 2023)
Sales promotion on impulsive buying, product quality on impulsive buying, sales promotion on shopping lifestyle, shopping lifestyle on impulsive buying, and sales promotion on impulsive buying mediated by shopping lifestyle are the subjects of this study. As independent variables, perceived price, sales promotion and product quality are used to determine variable (X). The dependent variable (Y) is impulse buying, and the intermediary variable (M) is shopping lifestyle. Quantitative research methods were used in this study, and Partial Least Square (PLS) – Structural Equation Modeling (SEM) was used to process the data. The examination was completed by a comfort check with a survey instrument using a Likert scale. By using Google form media, questionnaires were distributed online. Populace In this review, the client of skincare products from Shopee. Samples from In this study, 220 Generation Z people who live in Surabaya and are close to it who have bought skin care products at Shopee at least once participated. This study found that price perception has a positive and significant effect on impulsive purchases, sales promotion has a positive and significant impact on shopping lifestyle, product quality has a positive and significant effect on impulsive purchases, shopping lifestyle has a positive and significant impact on impulsive purchases, that sales promotion positive and significant effect on shopping lifestyle, and that shopping lifestyle mediates the impact of sales promotion on impulse buying.